National Health Service Bill : Summary of proposed new service (London : His Majesty's Stationery Office)
1946-03 1946 1940s 19 pages 15 77. The various functions comprised in the local government part of the health service are summarised below. Maternity and child welfare and midwifery 78. The Bill makes it the duty of every local health authority to make arrangements for the care of expectant and nursing mothers and of children under five years of age who are not attending school and who are therefore not covered by the school health service. Their arrangements will include ante-natal clinics for the care of expectant mothers, post-natal and child clinics, the provision of such things as cod-liver oil, fruit juices and other dietary supplements and, in particular, a priority dental service for expectant and nursing mothers and young children. 79. The Bill transfers these functions from such of the present "minor" authorities — the non-county boroughs and the district councils — as are at present exercising them. But, for co-ordination with the school health services, provision is made for delegating child welfare to "district executives" in the same way — and with the same rights for the minor authorities — as is done for the school health service under the Education Act, 1944. 80. The same authorities — county and county borough councils — are also made the supervising authorities for the purposes for the existing Midwives Acts; that is to say, they are made responsible for a complete midwifery service for mothers who are confined at home. The midwives are to be employed either by the local health authority itself or by voluntary organisations with whom the authority comes to an appropriate arrangement. Attendance at the confinement is not to be made the general duty of the doctor within the general medical practitioner service, but the midwife will have the usual right — and duty — to call in a suitably qualified doctor in case of need. The general practitioner's services will nevertheless be available to the ordinary extent of general advice and health care to a woman before and after confinement as at any other time. 81. Mothers who for any reason have their confinements in a hospital or maternity home will be in the care of the hospital and specialist service. It will also be the object of that service to provide locally for all specialist obstetric or gynaecological care which may be needed in relation to the ordinary domiciliary service of the local authority. The requirement of Ministerial approval to the local authority's arrangements will link together the two aspects of the maternity service — domiciliary and institutional. Health visiting and home nursing 82. It is made the duty of the local health authority to provide for a full health visitor service for all in their area who are sick, or expectant mothers, or those with the care of young children. This widens the present conception of health visiting (as concerned with mothers and children) into a more general service of advice to households where there is sickness or where help of a preventive character may be needed. 83. It is also made the duty of the local health authority to provide a home nursing service for those who — for good reason — need nursing in their own homes. 84. In both of these activities the local authority can, if it likes and if the Minister approves, make all or part of its provision by arrangement with voluntary organisations to act on its behalf. 292/847/4/115